Financial time series: Methods and models - Massimiliano Caporin; Giuseppe Storti (Journal of Risk and Financial Management, 2020)
The statistical analysis of financial time series is a rich and diversified research field whose inherent complexity requires an interdisciplinary approach, gathering together several disciplines, such as statistics, economics, and computational sciences. This special issue of the Journal of Risk and Financial Management on "Financial Time Series: Methods & Models" contributes to the evolution of research on the analysis of financial time series by presenting a diversified collection of scientific contributions exploring different lines of research within this field.
Keywords: 330; financial time series; GARCH models; capital markets; emerging markets; realized volatility; dynamic conditional correlation models; cointegration; model-based clustering; structural breaks; market efficiency; misery index